PENGARUH PRODUK DOMESTIK REGIONAL BRUTO, TINGKAT HUNIAN HOTEL, DAN JUMLAH WISATAWAN TERHADAP PENDAPATAN ASLI DAERAH DI KOTA BATU - Daffa Irham Asmynendar; Marseto Marseto; Sishadiyati Sishadiyati (Institute Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This study aims to determine the effect of Gross Regional Domestic Product, Hotel Occupancy Rate, and Number of Tourists on Regional Original Income in Batu City. The data used is time series data from 2009 to 2020. Based on the results of data analysis, it is concluded that the variables simultaneously Gross Regional Domestic Product, Hotel Occupancy Rate, and Number of Tourists have a significant and positive effect on Regional Original Income in Batu City. Partially, Gross Regional Domestic Product has a positive effect on Batu City's Original Revenue. While the Hotel Occupancy Rate, and the Number of Tourists have no significant effect on Regional Original Income in Batu City. Keywords: Local Revenue, Gross Regional Domestic Product, Hotel Occupancy Rate, Number of Tourists